Information Professionals: University of Porto Case Study - Pinto, Maria Manuela Gomes de Azevedo (2011)
This paper aims to present the information professional trained at the University of Porto (U.Porto), as the result of a paradigm shift brought on by the new field of Information Science. Following the surveys conducted, a comparative analysis of the results was performed, intersected with the characterization of the information professional's profile, thus typifying the information professionals graduating from the U.Porto. Some of the most important characteristics of the new information professional are highlighted, such as versatility, ability to summarize, knowledge diversity, adaptability, technological knowledge and ability to innovate. This study is relevant to any institution that trains information professionals at higher education level, as well as to potential employers and to the information professionals themselves. In despite of the small sample used in this study, it is an important basis to conduct more comprehensive studies and analyses on the impact on Portuguese society of the new and successful information professionals who have graduated from the U.Porto.